A truncated pre-F protein mRNA vaccine elicits an enhanced immune response and protection against respiratory syncytial virus - Min Lin; Yifan Yin; Xiaomeng Zhao; Chen Wang; Xueqing Zhu; Letao Zhan; Li Chen; Siling Wang; Xue Lin; Jun Zhang; Ningshao Xia; Zizheng Zheng (Nature Communications)
Abstract The Food and Drug Administration (FDA) has approved vaccines designed by GSK, Pfizer and Moderna to protect high-risk populations against respiratory syncytial virus (RSV). These vaccines employ the pre-fusion F (pre-F) protein as the immunogen. In this study, we explored an mRNA vaccine based on a modified pre-F protein called LC2DM-lipid nanoparticle (LC2DM-LNP). This vaccine features a truncated version of the pre-F protein that is anchored to the cell membrane. Our experiments in young and old female mice revealed that the LC2DM-LNP vaccine elicited robust neutralizing antibody titers. Moreover, LC2DM-LNP prompted a Th1-skewed T-cell immune response in female rodent models. Female cotton rats immunized with LC2DM-LNP demonstrated strong immunity to RSV, without signs of vaccine-enhanced respiratory disease (VERD), even in cases of breakthrough infection. Importantly, when administered to pregnant female cotton rats, LC2DM-LNP ensured the transfer of pre-F-specific antibodies to the offspring and provided protection against RSV without increasing lung inflammation. Our findings suggest that LC2DM-LNP could serve as an alternative RSV vaccine candidate for high-risk groups.